Preparation, characterization and in vitro photodynamic therapy of a pyropheophorbide-a-conjugated Fe3O4 multifunctional magnetofluorescence photosensitizer. Issue 44 (15th April 2016) - Cheng, Jianjun; Tan, Guanghui; Li, Wenting; Li, Jinghua; Wang, Zhiqiang; Jin, Yingxue
Abstract : Core–shell structure magneto-fluorescence chlorin pyropheorbide-a photosensitizer (MFNPs) with good water-dispersity and strong superparamagnetic for photodynamic therapy. Abstract : Novel pyropheophorbide-a-conjugated multifunctional magnetofluorescence nanoparticles Fe3 O4 @SiO2 @APTES@Glutaryl-PPa (MFNPs) with a mean diameter of 50 nm were strategically designed and prepared for photodynamic therapy (PDT) and medical fluorescence imaging. Chlorin photosensitizer pyropheophorbide-a (PPa) was covalently anchored on the surface of core–shell Fe3 O4 @SiO2 @APTES nanoparticles that were prepared via a sol–gel process with a bridging glutaryl group. The phase constitution, morphology, size, chemical properties, magnetic property of the intermediates and final nanoparticles were characterized by X-ray powder diffraction, transmission electron microscopy, Fourier transform infrared spectrometer, zeta potential, vibration sample magnetometer, thermogravimetric analysis, ultraviolet-visible absorption spectra and fluorescent emission spectroscopy. These results showed that the MFNPs have good dispersibility in alcohol and water, excellent magnetization with 17.31 emu g −1 at 300 K, strong superparamagnetic and good photoluminescence property. The in vitro PDT against the human HeLa cervical cancer cell suggested that MFNPs could permeate the tumor cells quickly and possess suitable lipo-hydro partition coefficient, inducing damage and apoptotic cell death. The cancer cell viability was lowered to 10.18% after treatment with PDT. In addition, the formation of reactive oxygen species in HeLa cells after MFNPs-PDT treatment was studied, which suggested that Type I and Type II photodynamic reactions can occur simultaneously.